CONFLICT MANAGEMENT WITHIN TRANSYLVANIA COLLEGE INTERNATIONAL SCHOOL - Maria-Daniela; Alexandru MORAR; George SUCIU (Cluj University Press, 2020)
The conflict has always been an inevitable progress and it existed since our earliest times whenever there was a desire to lead a group or even an empire. For this theme we took into account the fact that the term "conflict" has a negative connotation and it is often associated with concepts such as anger, aggressivity, opposition, although conflict doesn't necessarily need to be referred to as a negative experience. We must acknowledge the fact that if we experience conflicts in our lives, it means we are sincere, we express our visions, opinions, thoughts and feelings, and that, in this way, we can evolve and develop as humans. The objectives of the research within the international school Transylvania College Cluj-Napoca were to analyse the types of conflicts and what caused them within the organisation, the people who offered support to solve these conflicts and the number of conflicts each teacher had. For the research we used a survey where 37 teachers (males and females) replied to several questions in a google form at the end of the 2018 - 2019 academic year and where the responders had difficulties the researchers offered additional explanations by email or verbally. The study concluded that conflicts are not created because of the difference in objectives, but from the difference in how the parties involved want to achieve these objectives and the most common of the conflicts was definitely when people didn't express clearly what they wanted or gave unclear instructions. Furthermore, a clear communication reduces the differences in perception and the probability of a conflict. REZUMAT. Managementul conflictelor în cadrul Școlii Internaționale Transylvania College. Conflictul este un proces organizațional inerent, acesta a existat și există din cele mai vechi timpuri din dorința de a conduce, de a fi liderul unui grup sau al unui imperiu. În abordarea acestei teme am pornit de la premisa că termenul de conflict are o puternică conotație negativă, evocând cuvinte ca opoziție, mânie, agresivitate, acesta însă nu trebuie să fie neapărat înțeles ca fiind o experiență negativă deoarece acest concept dacă apare în viața noastră înseamnă că suntem oameni sinceri, care ne exprimăm opiniile și viziunile, cu ajutorul lui putem evolua și să ne îmbunătățim educația zilnic. Obiectivele cercetării din cadrul Școlii Internaționale Transylvania College Cluj-Napoca sunt de a depista cauzele si tipul de conflicte, persoanele din cadrul organizației care au oferit suport în rezolvarea conflictelor și numărul de conflicte avute de fiecare cadru didactic. Metoda anchetei a fost folosită în cadrul cercetării, unde un număr de 37 de cadre didactice gen masculin și feminin au răspuns la finalul anului școlar 2018-2019 unui chestionar în mod privat cu ajutorul platformei on-line google forms, iar unde au fost întâmpinate dificultăți s-au oferit explicații suplimentare prin email sau verbal. Studiul a concluzionat că, adesea, conflictele nu pornesc de la diferențe în privința obiectivelor sau scopurilor, ci de la modalitățile de atingere a acestora iar cauza cea mai des evidențiată la răspunsurile primite este neexprimarea clară și completă a uneia dintre părți. De asemenea comunicarea precisă reduce diferențele perceptuale și scade în acest mod probabilitatea de apariție a conflictului. Cuvinte cheie: conflict, obiectiv, management, lider.